Migraine in Obesity: Is It Prevalent? - Sabir Saeed , Aso; MohammadAmin Shukr, Osama (Diyala Journal of Medicine, 2020)
Background: Several studies have demonstrated an association between obesity and migraine. It’s still unclear whether migraine is the cause or it's the result of obesity. Objective: We investigated the prevalence of migraine among obese and non-obese individuals and analyzed the relationship between migraine prevalence and obesity. Patients and Methods: This is cross-sectional observational study was carried out at the neurology outpatients’ department of the Rizgary Teaching Hospital in Erbil, Iraq, from July 1st , 2018 to September 30, 2019. We interviewed and examined 300 persons, both obese (n=154) and non-obese (n=146), and of both gender. All of them were adults (>18 years old). Each person's weight, height, body mass index (BMI), and waist circumference were measured.The diagnosis of migraine was made according to the International Headache Society’s criteria. Obesity was present if the individual’s BMI is ≥30 and/or waist-to-hip ratio is >0.9 in females and >1.0 in males. Results: Out of the 300 persons, 14 males (8.5%) got migraines while migraine was found in 37 females (27.4%), irrespective of their weight. Out of the 300 persons, the prevalence of migraine among obese individuals was 21.4% (n=33) and while in non-obese individuals was 12.3% (n=18). There was a statistically significant difference between the groups (p-value=0.045). The overall prevalence of migraine was 16.9% of the persons interviewed. Conclusion: The results showed that migraine is more prevalent among obese persons than non-obese persons and the difference was statistically significant.